Relationship between progression of visual field defect and intraocular pressure in primary open-angle glaucoma - Naito T (Dove Medical Press, 2015)
Tomoko Naito,1 Keiji Yoshikawa,2 Shiro Mizoue,3 Mami Nanno,4 Tairo Kimura,5 Hirotaka Suzumura,6 Fumio Shiraga1 1Department of Ophthalmology, Okayama University Graduate School of Medicine, Okayama, Japan; 2Yoshikawa Eye Clinic, Tokyo, Japan; 3Department of Ophthalmology, Ehime University Graduate School of Medicine, Ehime, Japan; 4Kagurazaka Minamino Eye Clinic, 5Ueno Eye Clinic, 6Suzumura Eye Clinic, Tokyo, Japan Purpose: To analyze the relationship between intraocular pressure (IOP) and the progression of visual field defects in Japanese primary open-angle glaucoma (POAG) and normal-tension glaucoma (NTG) patients.Patients and methods: The subjects of the study were patients undergoing treatment for POAG or NTG who had performed visual field tests at least ten times with a Humphrey field analyzer (Swedish interactive thresholding algorithm standard, C30-2 program). The progression of visual field defects was defined by a significantly negative value of the mean deviation slope at the final visual field test during the follow-up period. The relationships between the progression of visual field defects and IOP, as well as other clinical factors, were retrospectively analyzed.Results: A total of 156 eyes of 156 patients were included in the analysis. Significant progression of visual field defects was observed in 70 eyes of 70 patients (44.9%), while no significant progression was evident in 86 eyes of 86 patients (55.1%). The eyes with visual field defect progression had significantly lower baseline IOP (P<0.05), as well as significantly lower IOP reduction rate (P<0.01). The standard deviation of IOP values during follow-up was significantly greater in the eyes with visual field defect progression than in eyes without (P<0.05).Conclusion: Reducing IOP is thought to be useful for Japanese POAG or NTG patients to suppress the progression of visual field defects. In NTG, IOP management should take into account not only achieving the target IOP, but also minimizing the fluctuation of IOP during follow-up period. Keywords: primary open-angle glaucoma, normal-tension glaucoma, intraocular pressure, progression of visual field defects, MD slope